Acute Decompensated Heart Failure pada Pasien Wanita 41 Tahun dengan Chronic Kidney Disease Stadium V: Laporan Kasus - Amanda Dewi Rosita; Fajar Yuwanto (Medula, 2026)
Acute decompensated heart failure (ADHF) is a cardiovascular emergency that frequently occurs in patients with advanced chronic kidney disease (CKD) due to impaired fluid regulation, electrolyte imbalance, and cardiorenal syndrome. This condition increases the risk of acute pulmonary congestion, severe metabolic disturbances, and reduced tissue perfusion, which may be life-threatening. A 41-year-old woman with stage V CKD presented with progressive acute dyspnea, orthopnea, paroxysmal nocturnal dyspnea, and decreased activity tolerance for several days before hospital admission. Physical examination revealed tachypnea, hypertension, peripheral edema, bilateral basal crackles, and elevated jugular venous pressure. Laboratory findings showed severe anemia, hyperkalemia, metabolic acidosis, and elevated urea and creatinine levels, while chest radiography demonstrated cardiomegaly and pulmonary congestion. Electrocardiography and echocardiography supported the presence of cardiac dysfunction that aggravated the clinical condition. Based on clinical and diagnostic findings, the patient was diagnosed with acute decompensated heart failure with pulmonary congestion in the setting of stage V CKD. Management included oxygen therapy, fluid restriction, intravenous loop diuretics, nitroglycerin, correction of metabolic abnormalities, and packed red cell transfusion. Due to persistent fluid overload and severe metabolic disturbances unresponsive to conservative treatment, emergency hemodialysis was planned as definitive therapy. ADHF in patients with stage V CKD is a serious condition that requires early detection, comprehensive evaluation, and multidisciplinary management. Renal replacement therapy plays a crucial role in improving hemodynamic stability, reducing fluid burden, and preventing recurrent decompensation.